Appendiceal Goblet Cell Carcinoid: An Unexpected Histology Following Simple Appendicectomy - Rosli Ismail; Mohd Firdaus Che Ani; Salahuddin Baharom; Nornazirah Azizan; Andee Dzulkarnaen Zakaria; Mohd Firdaus Mohd Hayati (Gazi Universitesi, 2022)
Goblet cell carcinoid (GCC) is an enigmatic and rare tumour involving the appendix almost exclusively. It is a rare, aggressive subtype of appendiceal tumours with neuroendocrine features, and controversy exists with regards to therapeutic strategy. We herein highlight a 56-year-old lady with GCC whom she presented initially with a typical presentation of acute appendicitis. The histologic hallmark of this entity is the presence of clusters of goblet cells in the lamina propria or submucosa stain for various neuroendocrine markers, though the intensity is often patchy. GCC of the appendix is rare and challenging. In advanced form, it can present with carcinoid symptoms but occasionally mimics classical presentations of acute appendicitis. A tumour measuring less than 1 cm and located at the tip of the appendix is sufficient for a simple appendicectomy which warrants a promising prognosis.